Assessment of vitamin A status in chronic obstructive pulmonary disease patients and healthy smokers - Paiva, Sergio Alberto Rupp de [UNESP]; Godoy, Irma de [UNESP]; Vannucchi, Hélio; Fávaro, Rosa M. D.; Geraldo, Rosana R. C.; Campana, Alvaro O. (My University, 1996)
The relation between vitamin A status and the degree of lung airway obstruction was examined in a cross-sectional study of 36 male subjects aged 43-74 y who were assigned to five groups as follows: healthy nonsmokers (n = 7), healthy smokers (n = 7), mild chronic obstructive pulmonary disease (COPD-mild) patients (n = 9), COPD-moderate-severe patients (n = 7), and COPD-moderate-severe patients with exacerbation (+ex; n = 6). Smoking habits, pulmonary function tests, and energy-protein status were assessed; serum concentrations of retinyl esters, retinol, retinol binding protein, and transthyretin and relative dose responses were measured. In addition, 12 male smokers aged 45-61 y with mild COPD were randomly assigned to two groups for a longitudinal study: six subjects consumed vitamin A (1000 RE/d; COPD- vitamin A) and six subjects received placebo for 30 d. Lowered serum retinol concentrations were found in the COPD-moderate-severe and COPD-moderate- severe+ex groups. Measurements of vitamin A status in healthy smokers and in COPD-mild patients were not different from those in healthy nonsmokers. The improvement of pulmonary function test results after vitamin A supplementation [mean increase for 1-s forced expiratory volume (FEV1) = 22.9% in the COPD-vitamin A group] may support the assumption of a local (respiratory) vitamin A deficiency in patients with this disease.
Keywords: chronic obstructive pulmonary disease; pulmonary function tests; retinol circulating complex; Vitamin A status assessment; acute phase protein; albumin; alpha carotene; beta carotene; c reactive protein; ceruloplasmin; placebo; prealbumin; retinol binding protein; retinol ester; retinol palmitate; airway obstruction; chronic obstructive lung disease; cigarette smoking; clinical protocol; clinical trial; controlled clinical trial; controlled study; diet supplementation; disease severity; forced expiratory volume; lung function test; nutritional status; oral drug administration; randomized controlled trial; retinol deficiency; vitamin blood level; Analysis of Variance; Carotenoids; Cross-Sectional Studies; Diet; Intestinal Absorption; Liver; Longitudinal Studies; Lung; Lung Diseases, Obstructive; Middle Aged; Nutritional Status; Respiratory Function Tests; Smoking; Vitamin A; Vitamin A Deficiency